First fossil representatives of Pharaxonothinae Crowson (Coleoptera: Erotylidae): indirect evidence for cycads existence in Baltic amber forest - Alekseev, Vitalii I.; Bukejs, Andris (Zootaxa, 2017)
A new species of Erotylidae, Cycadophila (s. str.) mumia sp. nov., the first fossil representative of the subfamily Pharaxo-nothinae, is described and illustrated from Eocene Baltic amber. A second closely related specimen is reported but not described as new due to poor preservation in amber. The occurrence of representatives of the Recent cycad-specialized genus in Baltic amber can indirectly indicate the presence of their host plants (Cycadales: Cycadophyta: Cycadopsida) in the Eocene amber forest.